Consumo de sustancias adictivas en los estudiantes del colegio Fernando Suarez Palacio de la ciudad de Loja - Cabrera Esparza, Ligia Verónica (2023)
In recent years, the use of psychoactive substances has become a daily practice of many young people, generating a public and social health problem. The main objective of this research work was to determine the consumption of addictive substances in the students of "Fernando Suárez Palacio" school in Loja city, The ASSIST questionnaire, consisting of eight questions and sub-questions, was applied to characterize socio-demographically the population of 149 students of the school, which allowed finding the difference in the consumption of each substance between men and women, also to know the level of risk, and its classification according to the level of consumption: low, moderate or high. The results obtained were that the highest consumption of addictive substances occurs in students between 14 and 16 years of age, which is equivalent to 43.62% (n=65), the most consumed substances according to the sex of the respondents is tobacco, with a predominance of male sex in 64.71% (n=73) followed by alcohol, which corresponds to 52.73% (n=73). It is concluded that among the most important risk factors is the easy access to tobacco and alcoholic beverages, which may influence the consumption of psychoactive substances at an early age